Two CCAAT‐box‐binding transcription factors redundantly regulate early steps of the legume‐rhizobia endosymbiosis. (28th July 2014) - Laloum, Tom; Baudin, Maël; Frances, Lisa; Lepage, Agnes; Billault‐Penneteau, Benjamin; Cerri, Marion R.; Ariel, Federico; Jardinaud, Marie‐Françoise; Gamas, Pascal; de Carvalho‐Niebel, Fernanda; Niebel, Andreas
Summary During endosymbiotic interactions between legume plants and nitrogen‐fixing rhizobia, successful root infection by bacteria and nodule organogenesis requires the perception and transduction of bacterial lipo‐chitooligosaccharidic signal called Nod factor (NF). NF perception in legume roots leads to the activation of an early signaling pathway and of a set of symbiotic genes which is controlled by specific early transcription factors (TFs) including CYCLOPS/IPD3, NSP1, NSP2, ERN1 and NIN. In this study, we bring convincing evidence that the Medicago truncatula CCAAT‐box‐binding NF‐YA1 TF, previously associated with later stages of rhizobial infection and nodule meristem formation is, together with its closest homolog NF‐YA2, also an essential positive regulator of the NF‐signaling pathway. Here we show that NF‐YA1 and NF‐YA2 are both expressed in epidermal cells responding to NFs and their knock‐down by reverse genetic approaches severely affects the NF‐induced expression of symbiotic genes and rhizobial infection. Further over‐expression, transactivation and ChIP‐PCR approaches indicate that NF‐YA1 and NF‐YA2 function, at least in part, via the direct activation of ERN1. We thus propose a model in which NF‐YA1 and NF‐YA2 appear as early symbiotic regulators acting downstream of DMI3 and NIN and possibly within the same regulatory complexes as NSP1/2 to directly activate the expression of ERN1.